Intellectual property protection intensity and regional technological innovation structure: Based on the perspective of economic complexity theory - Qingfeng Luo; Xi Zhao (Heliyon)
Exploring the intrinsic link between the intensity of intellectual property protection and the optimization of regional technological innovation structure from the perspective of economic complexity theory. Using panel data and employing the dual fixed effects estimation method, we empirically examine the impact of intellectual property protection strength on innovation factors, the innovation environment, and innovation output. Our study finds that intellectual property protection has a positive incentive effect on knowledge acquisition, knowledge creation, the innovation environment, and substantive innovation, while it inhibits non-substantive innovation. Strong intellectual property protection effectively promotes the optimization of innovation factors, the innovation environment, and innovation output structures, thereby driving the optimization of the regional technological innovation structure. In terms of impact magnitude, the order from high to low is: knowledge creation, substantive innovation, innovation environment, knowledge acquisition, and non-substantive innovation. The “optimal intensity” of intellectual property protection significantly promotes the optimization of the regional technological innovation structure, whereas excessively strong or weak intellectual property protection hinders this optimization. Implementing a strategy of innovation-driven development requires further reform and improvement of the national intellectual property protection system to establish the optimal intensity of protection and promote the optimization of the regional technological innovation structure.